APLIKASI ANDROID SEBAGAI PENGONTROL JARAK JAUH SMARTHOME DENGAN KONEKSI JARINGAN INTERNET - Hesti, Emilia; Adewasti, Adewasti (JURNAL SURYA ENERGY, 2018)
In the modern era of technology is growing very rapidly, especially the use of Internet media in everyday activities. At this time developed a concept called Internet of Things (IoT). Internet of Things (IoT) is a concept that aims to expand the benefits of internet connectivity that is connected continuously. The Internet of Things (IoT) can be utilized at home to control electronic equipment such as lamps, fans and can also be used in home security systems such as automatic door locks and remote controlled gates through applications on the Android system. Control can be done anywhere as long as there is internet connection and applications used can be installed on all smartphones that have android operating system. Research is done by utilizing the Web service that has been available for free called Teleduino. This web service that serves as an intermediary between the Android device and Arduino microcontroller. In Arduino Microcontroller an additional device called Ethernet Shield is needed to connect the Arduino to the Internet directly connected to Teleduino's web service.